RESEARCH ON WATER ACTIVITY INDEX IN FROZEN MEAT FOODS - Morgunova A.V. (Техника и технология пищевых производств)
The article deals with a science intensive technology of fast-frozen dishes production with the use of activated liquids and systems. The objective of this research is to investigate the measurement of water activity in the developed frozen meat products. A receipt of fast-frozen dishes includes sausage goods and a vegetable garnish. The sausage goods are made of beef, pork, dried milk, starch, protein-fat emulsion and gel based on the «Kat-gel 95» protein preparation. The water used is treated in the apparatus of «Izumrud» type, obtaining acid and alkaline fractions with a specified level of pH. Their further activation is done using a commercial sound processor «Hielscher Ultrasound Technology UP». Activated liquids obtained have pronounced bactericidal and antiseptic qualities, thus promoting prolonged shelf life of finished goods. The research is done using the analytic and organoleptic methods, the method of measurement, the method of calculation and the expert one. To determine the water activity index we use samples defrosted after thirty days of storing. The values of water activity indices are determined separately for fast-frozen dishes produced with the use of activated liquid systems and for control samples produced with the use of tap potable water. According to the results of the water activity index determination it has been established that the samples produced with the use of activated liquids and systems have the index of 0.9638. The water activity index of the control samples appears to be higher by 0.0198 units in comparison with the samples produced with the use of activated liquids. This fact indicates that water has a stronger connection with non-aqueous components during activation of aqueous systems when producing foods. Consequently, water has a lower possibility to support processes leading to goods spoilage.